2010
DOI: 10.1080/09687591003701355
|View full text |Cite
|
Sign up to set email alerts
|

‘Away with the fairies?’ Disability within primary‐age children's literature

Abstract: This article outlines the findings of a new study that explores the portrayal of disability within a sample of the primary-age children's literature most readily available to UK schools. The kind of literature to which children are exposed is likely to influence their general perceptions of social life. How disability is handled by authors is therefore important from the standpoint of disability equality. Findings suggest that whilst there are some good examples of inclusive literature 'out there', discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 20 publications
0
31
0
8
Order By: Relevance
“…Extant research indicates that negative conceptualisations may be formed by exposure to the ‘picture’ of disability created by parental attitudes (Deal, 2003), the media (Barnes, 1992), children's literature (Pederson, 2003), peer interaction (Shakespeare, 1994) and children's textbooks (Hodkinson, 2007). To be specific, Leicester (2007) suggests children's literature by absenting characters who are disabled, evokes a message that disabled people are less interesting and of less value than other members of our society (Beckett et al., 2010). Additionally, Hodkinson (2007) concluded that the representation of disability in school textbooks was limited and ‘infected with models of child deficit’ (Clough, 2005, p. 74).…”
Section: New Labour's Inclusion: Conceptually Naive?mentioning
confidence: 99%
See 1 more Smart Citation
“…Extant research indicates that negative conceptualisations may be formed by exposure to the ‘picture’ of disability created by parental attitudes (Deal, 2003), the media (Barnes, 1992), children's literature (Pederson, 2003), peer interaction (Shakespeare, 1994) and children's textbooks (Hodkinson, 2007). To be specific, Leicester (2007) suggests children's literature by absenting characters who are disabled, evokes a message that disabled people are less interesting and of less value than other members of our society (Beckett et al., 2010). Additionally, Hodkinson (2007) concluded that the representation of disability in school textbooks was limited and ‘infected with models of child deficit’ (Clough, 2005, p. 74).…”
Section: New Labour's Inclusion: Conceptually Naive?mentioning
confidence: 99%
“…A key success criterion for inclusion was that parents of children with special educational needs (SEN) and/or those who are disabled would have confidence that mainstream schools would provide high‐quality education and enable all pupils to become valued members of the school community (Department for Education and Science (DfES), 2004). In 2006, the Disability Equality Duty became the ‘stick’ which further ‘encouraged’ the evolution of inclusion as it created a legal framework so that schools were now compelled to discuss and confront harassment, stereotyping and discrimination as well as promoting positive attitudes towards disabled people (Beckett, Ellison and Barrett et al., 2010).…”
mentioning
confidence: 99%
“…Hughes' research concluded that teachers still need to be much more selective as to which non-fiction books they incorporate into their classroom resources. Beckett et al's (2010) research demonstrates that in the twenty-first century representations of disability and impairment seemingly had changed little to those dominating the preceding century. Beckett's findings confirming those of Reiser and Mason (1992) denote that discriminatory language and negative stereotypes continue to be folded into representations of disability appearing in children's literature.…”
Section: Aq9mentioning
confidence: 99%
“…Despite this more positive work, it is interesting to note the study of Hughes (2006) AQ10 ¶ and Beckett et al (2010). Hughes' study examined the representation of visual impairment in six picture books designed for children aged 12 or under.…”
Section: Aq9mentioning
confidence: 99%
See 1 more Smart Citation